Psychometric validation of Young's Internet Addiction Test among Chinese undergraduate students. - Zhixia Wei; Norlizah Che Hassan; Siti Aishah Hassan; Normala Ismail; Xiaoxia Gu; Jingyi Dong (PLoS ONE)
The global prevalence of internet addiction is escalating annually and uncontrollable use of the internet can cause significant physical and psychological damage. Young's Internet Addiction Test (IAT), widely utilized across diverse cultures, has demonstrated structural inconsistencies in previous research, with some items requiring refinement. This study aimed to validate the IAT among Chinese undergraduate students and assess its psychometric properties. The IAT's structure was initially explored through Exploratory Factor Analysis (EFA) using pilot study data (n=376), with internal consistency and test-retest reliability (n=96) evaluated. Subsequently, Confirmatory Factor Analysis (CFA) was conducted using data from the actual study (n=1042) to confirm the structure. Results showed that a three-factor solution explained 61.29% of the total variance with a satisfactory model fit (χ2/df = 4.382, RMSEA = 0.057, CFI = 0.952, TLI = 0.943, SRMR = 0.045, AIC = 798.755) and psychometric properties, validating the IAT's utility for future investigations of internet addiction in Chinese undergraduates. Notably, a high prevalence of moderate internet addiction was observed within the sample, highlighting the significance of this issue in the target population and emphasizing the need for further research and potential interventions.